Reviews and Responses for Open Machine Learning Models for Actual Takeoff Weight Prediction - Murça, Mayara Condé Rocha; Ricardo Omena de Albuquerque Maximo, Marcos; de Andrade Dantas, João Paulo; Tarelho Szenczuk, João Basílio; Rutili de Lima, Carolina; Orbolato Carvalho, Lucas; de Melo, Gabriel Adriano; Alligier, Richard; Mori, Ryota; Sun, Junzi (Journal of Open Aviation Science, 2025)
Detailed reviews and responses can be found in the PDF and HTML versions of this document. The DOI for the original paper is https://doi.org/10.59490/joas.2025.7963